Konsep Ideal Protein (Asam amino) Fokus Pada Ternak Ayam Pedaging (review artikel) - Samadi Samadi (Agricultural Faculty, 2012)
Ideal protein (amino acids) concept focused on broiler ABSTRACT. Accurate estimation of the amino acid requirement is very importance for diet formulation in growing animals such as broiler. Inadequate formulation of dietary amino acids will impair protein utilization and increase the total nitrogen output to the environment. Amino acids requirement of animals changes due to dietary, sex, and genetic and environmental factors. To address all potential combinations of factors with dose-response experiments is almost impossible. Thus the ideal protein concept provides a simple and effective approach to solve this problem. Based on this concept, the requirement of indispensible amino acids can be determined. For this concept, lysine has been used as the reference amino acid to calculate other indispensable amino acids due to several considerations. This paper will review more detailed about protein concept based on amino acid profile by using broiler as sampel review.